The Role of Stereotactic Ablative Radiotherapy in Oncological and Non-Oncological Clinical Settings: Highlights from the 7th Meeting of AIRO – Young Members Working Group (AIRO Giovani). Issue 6 (November 2014) - Franco, Pierfrancesco; De Bari, Berardino; Ciammella, Patrizia; Fiorentino, Alba; Chiesa, Silvia; Amelio, Dante; Pinzi, Valentina; Bonomo, Pierluigi; Vagge, Stefano; Fiore, Michele; Comito, Tiziana; Cecconi, Agnese; et al.
Stereotactic ablative radiotherapy is a modern cancer treatment strategy able to deliver highly focused radiation in one or a few fractions with a radical intent in several clinical settings. Young radiation oncologists need a constant and tailored update in this context to improve patient care in daily clinical practice. A recent meeting of AIRO Giovani (AIRO - Young Members Working Group) was specifically addressed to this topic, presenting state-of-the-art knowledge, based on the latest evidence in this field. Highlights of the congress are summarized and presented in this report, including thorough contributions of the speakers dealing with the role of stereotactic ablative radiotherapy in both oncological and non-oncological diseases, divided according to anatomical and clinical scenarios: intra-cranial settings (brain malignant primary tumors, metastases, benign tumors and functional disorders) and extra-cranial indications (lung primary tumors and metastases, thoracic re-irradiation, liver, lymph node and bone metastases, prostate cancer). With literature data discussed during the congress as a background, stereotactic ablative radiotherapy has proved to be a consolidated treatment approach in specific oncological and non-oncological scenarios, as well as a promising option in other clinical settings, requiring a further prospective validation in the near future. We herein present an updated overview of stereotactic ablative radiotherapy use in the clinic.